2013
DOI: 10.1155/2013/971841
|View full text |Cite
|
Sign up to set email alerts
|

Low-Grade Inflammation and Spinal Cord Injury: Exercise as Therapy?

Abstract: An increase in the prevalence of obesity in people with spinal cord injury can contribute to low-grade chronic inflammation and increase the risk of infection in this population. A decrease in sympathetic activity contributes to immunosuppression due to the lower activation of immune cells in the blood. The effects of physical exercise on inflammatory parameters in individuals with spinal cord injury have not been well described. We conducted a review of the literature published from 1974 to 2012. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…17 Other forms of plasticity within the nervous system, such as hippocampal long-term potentiation and spinal instrumental learning, are also inhibited in the presence of systemic inflammation. [18][19][20] Several studies report that chronic SCI is associated with a low-grade, systemic inflammatory state in the absence of active infections or pressure sores; [21][22][23] suggesting that AIHinduced plasticity may be impaired in individuals with chronic SCI. Accordingly, we tested the hypothesis that pre-treatment with an anti-inflammatory drug will enhance the ability of AIH to induce spinal motor plasticity in humans with chronic SCI.…”
Section: Introductionmentioning
confidence: 99%
“…17 Other forms of plasticity within the nervous system, such as hippocampal long-term potentiation and spinal instrumental learning, are also inhibited in the presence of systemic inflammation. [18][19][20] Several studies report that chronic SCI is associated with a low-grade, systemic inflammatory state in the absence of active infections or pressure sores; [21][22][23] suggesting that AIHinduced plasticity may be impaired in individuals with chronic SCI. Accordingly, we tested the hypothesis that pre-treatment with an anti-inflammatory drug will enhance the ability of AIH to induce spinal motor plasticity in humans with chronic SCI.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the cytoskeletal protein GFAP is closely related to the inflammatory response [3]. Microglia and macrophages release inflammatory cytokines involved in the initial reaction, such as tumor necrosis factor alpha (TNF-a) and interleukin-1 beta (IL-1b) [4]. These inflammatory cytokines can activate astrocytes, which then secrete more inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…By considering the proposed mechanisms of o-3 PUFA in induction of neurorecovery, which originate mostly from its anti-oxidative and anti-inflammatory effects, 18 it is expectable to observe noticeable influence in acute phase of injury when these inflammatory reactions are at their peak level. Previous literatures has supported the fact that a state of chronic inflammation occurs after SCI 19,20 and this steady inflammation even explained higher risk of atherogenic events in these patients. 20 Some studies have also demonstrated that alterations in immune system in spinal cord-injured patients may contribute in this low-grade inflammatory process.…”
Section: Discussionmentioning
confidence: 67%